Jordan Workforce Development : SABER Country Report 2013 - World Bank (Washington, DC, 2014)
Human Development in Jordan has witnessed significant progress over the past two decades, in line with Jordan s vision to become a regional leader through leveraging its strong human capital base into a skills, knowledge and innovation driven economy. Evidence of progress on this front is provided by the advancement of the country s human development and education indicators. Between 1980 and 2011, the Human Development Index (HDI) value increased by 29 percent, the adult literacy rate reached 92.6 percent; the primary school completion rate hit 100 percent and combined gross enrolment reached 79 percent. In the decade prior to the global financial slowdown of 2008 and the subsequent political unrest in the region, Jordan experienced rapid economic growth, outperforming the MENA average.